The Relationship between Physical Health and Psychological Well-Being among Oldest-Old Adults - Jinmyoung Cho; Peter Martin; Jennifer Margrett; Maurice MacDonald; Leonard W. Poon (Journal of Aging Research)
The purpose of this study was to evaluate the relationship between physical health and psychological well-being among oldest-old adults. Structural equation modeling was performed to examine health influences on psychological well-being among 306 octogenarians and centenarians from the Georgia Centenarian Study. Latent variables were created to reflect subjective health, as measured by self-ratings of health and objective health, as measured by physical health impairment (i.e., health problems, past and present diseases, hospitalization) and biomarkers (i.e., hemoglobin and albumin). Psychological well-being was measured by positive and negative affect. There were significant direct effects of subjective health on affect and significant indirect effects of objective health through subjective health on positive affect and negative affect. Subjective health took the role of a mediator between objective health and psychological well-being. These results highlight the status and perceptions of health as a critical indicator for well-being in extreme old age.